4D printing of mechanically robust PLA/TPU/Fe3O4 magneto-responsive shape memory polymers for smart structures. (1st January 2023) - Liu, Han; Wang, Feifan; Wu, Wenyang; Dong, Xufeng; Sang, Lin
Abstract: The integration of magneto-responsive shape memory polymers (SMPs) into 4D printing provides novel opportunities to create innovative and intelligent products controlled in a contactless method. In this study, a promising SMPs with robustly mechanical property and magneto-responsive behavior were proposed and fabricated into 3D printing feedstock based on polylactic acid (PLA), thermoplastic polyurethane (TPU) and Fe3 O4 particles. Results revealed that the 3D-printed PLA/TPU/Fe3 O4 possessed robust tensile strength and modulus with a homogeneous distribution of magnetic particles in polymer blends. Also, PLA/TPU/Fe3 O4 exhibited excellent shape fix ratio (∼100%), recovery ratio (>91%) and rapid magnetic response within as short as 40 s, suggesting the high efficiency of heat generation by magnetic particles. Moreover, smart structures including honeycomb and bionic flower-like model were designed and printed as an original shape. After programmed by an external force, the folded lattice structure at the temporary shape could recovered completely under a contactless magnetic field. The flower-bud structure sequentially restored layer-by-layer controlled by using three pedals with varied Fe3 O4 composites. Consequently, the high-load capacity, fast magneto-responsive behavior and high recovery performance of the proposed multi-material have great potentials in actuator or robots applications via 3D printing. Highlights: Magnetic PLA/TPU/Fe3 O4 as composite filaments for fused filament fabrication (FFF) technique. Fast magneto-responsive shape memory and recovery behavior by heat or magneto stimulation. Facile transformation between designed structures with temporary shape and magneto-stimulated into original shape.